PRIMING THE CHARITABLE PUMP: AN EXPERIMENTAL INVESTIGATION OF TWO‐STAGE RAFFLES. (21st July 2015) - Goerg, Sebastian J.; Lightle, John P.; Ryvkin, Dmitry
Abstract : We experimentally study two‐stage self‐financing raffles in which participants can buy tickets in two stages. In all raffles, one half of the proceeds are donated to a local charity and the raffle winner wins the other half. The mechanisms differ by what happens to the tickets purchased in the first stage. In the complete draw down two‐stage raffle, the first stage tickets are eliminated from the active pool of tickets, while in the no draw down raffle they remain in the active pool. We find that both two‐stage raffles initially perform better than the standard one‐stage 50–50 raffle. Over time, the aggregate contribution level in the complete draw down raffle declines and approaches that of the one‐stage raffle, while in the no draw down raffle contributions are stable and remain higher than those in the other two mechanisms. In both two‐stage raffles, we observe a positive correlation between the proceeds of the first stage and the number of tickets bought in the second stage. Our results are at odds with a standard warm glow model of giving, and also cannot be explained by the joy of winning or learning about bidders' types. ( JEL C72, C92, D64)